Physical Function–Tardive Dyskinesia (PATD) on Critical Patients in Intensive Care Unit - Heru Suwardianto; Selvia David Richard; Awal Prasetyo; Reni Sulung Utami (Jurnal Ners, 2017)
Introduction: Critical patients are patients who potentially get reversible dysfunction in one or more life-threatening organs and require care in the Intensive Care Unit (ICU).Methods: The objective of this research is to analyse the physical function-tardive dyskinesia in critical patients with sedation in the ICU. The design of this research is cross-sectional. The population is all of the critical patients in the ICU of the Baptist Hospital in Kediri. The purposive sample population was 41 respondents based on the inclusion and exclusion criteria. The variables are ‘giving the sedation’ and ‘physical function-tardive dyskinesia’. The data was collected using a Motor Activity Assessment, and the Sedation Scale for Critically Ill Patients and Tardive Dyskinesia Screening.Results: The results showed that giving sedation can slow physical function in the form of motor activity; the response of noxious stimuli (7.3%), response to touch or calling name (19.5%) and an increasing score of agitation and co-operative (4.9%). Symptoms of tardive dyskinesia increased after sedation in the form of tongue protrusion (4.9%), lip-smacking, puckering and pursing (2.4%), and rapid movements of the arms and legs. The administration of sedation in the first 24-hours in ICU patients affects the physical function of the critical patients (p = 0.005). Conclusion: Giving sedation affects the patients’ physical functions. Therefore, the prevention of the effects of sedation and treatment during ICU is needed in order to avoid a decrease in the physical function of critical patients.